2008
DOI: 10.1111/j.1365-2044.2007.05402.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre‐operative anxiety on induction of anaesthesia with propofol*

Abstract: Summary In this prospective study, we investigated the effects of anxiety on the induction dose of propofol and subsequent cardiovascular changes in 197 patients. Pre‐operative state and trait anxiety scores were measured using the State Trait Anxiety Inventory. Propofol was administered at 40 mg.kg−1.h−1. Propofol dose was recorded at loss of verbal response and when EEG Bispectral Index decreased to 50. Thereafter, propofol infusion rate was reduced to 8 mg.kg−1.h−1. Cardiovascular data were collected for 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
(39 reference statements)
3
20
0
Order By: Relevance
“…We also observed that STAI-S measured in the operating room had a strong positive correlation with HR ( Figure 5). This is in agreement with Morely et al 9 and Gras S et al 10 Conflicting results have been reported in the previous studies concerning the effects of anxiety on Propofol dose requirement for induction. Maranets et al found that increased preoperative STAI-T on the day of surgery was associated with higher Propofol bolus dose to achieve a BIS (bispectral index) value between 40 and 60.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also observed that STAI-S measured in the operating room had a strong positive correlation with HR ( Figure 5). This is in agreement with Morely et al 9 and Gras S et al 10 Conflicting results have been reported in the previous studies concerning the effects of anxiety on Propofol dose requirement for induction. Maranets et al found that increased preoperative STAI-T on the day of surgery was associated with higher Propofol bolus dose to achieve a BIS (bispectral index) value between 40 and 60.…”
Section: Discussionsupporting
confidence: 92%
“…9 Gras S et al found no strong correlation between state and trait anxiety with propofol dose requirement for loss of consciousness (LOC). 10 They found significant positive correlation between HR in the operating room and propofol dose and also between STAI-S in the operating room and HR, thereby supporting an indirect effect of pre-anesthetic anxiety through changes in the HR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This is a validated tool for self-reporting anxiety, already used during the perioperative period. [1][2][3]14 It comprises 2 sets of 20 statements.…”
Section: Assessment Of Anxietymentioning
confidence: 99%
“…1,2 However, this assumption has been recently challenged. 3 Some studies that investigated the effects of perioperative anxiety recorded the propofol dose required to obtain loss of consciousness (LOC) or a defined level of sedation 1,2 but did not consider the hemodynamic effects of anxiety. Anxiety and acute mental stress are associated with increased heart rate (HR) and cardiac output.…”
mentioning
confidence: 99%